72A Nonshaven Follicular Unit Extraction Techniques (Hair Transplantation, 2023)
Nonshaven follicular unit excision (NS-FUE), by definition, does not require shaving of the donor area, which is one of the least convenient aspects of FUE. Patients not only wish for less postoperative pain and an unnoticeable scar but also do not want to be shaven. Patient satisfaction will be greater if FUE can be done without shaving. NS-FUE has come to light owing to the efforts of many surgeons who endeavored to solve the problem. There are two main ways of conducting NS-FUE: the direct method and pretrimming method. However, all subtypes of NS-FUE involve successful punch insertion and excision at the same time setting aside numbers of long hairs; this requires a great deal of extra effort and takes time to perform with efficiency and skill. Overcoming surgical barriers of NS-FUE will bring more satisfaction to patients. This chapter deals with choosing the best instruments and methods and the proper indication for successful NS-FUE.
Keywords: nonshaven FUE; direct method; pretrimming method; Boaventura punch; open punch; open-window punch; NS-FUE